2004
DOI: 10.1001/archsurg.139.9.954
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Correlates With Mortality in Early-Stage Breast Cancer

Abstract: Hypothesis: Body weight correlates with risk of breast cancer death. Design: A retrospective cohort study using patient medical records, electronic cancer registry data, and archived tissue specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 27 publications
3
41
0
1
Order By: Relevance
“…35 Brown et al demonstrated a positive association between obesity and MM, 36 an association that echoes findings in other cancers characterized by a deregulated prostaglandin network, such as breast and colo-rectal. 37,38 The link between obesity and prostaglandin metabolism has several potential explanations, including increased availability of substrate and IGF (insulin growth factor)-mediated up-regulation of prostaglandin metabolism. 39 Finally, the beneficial properties of some drugs employed in the treatment of MM, most notably thalidomide and immunomodulatory drugs (IMiDs) might also depend on effective inhibition of the COX-2 pathway, as outlined in a recent paper by Fujita et al 40 COX-2 involvement in MM is obviously a strong indication of this pathway's potential role in other hematologic cancers, but the literature is limited in this field.…”
Section: Discussionmentioning
confidence: 99%
“…35 Brown et al demonstrated a positive association between obesity and MM, 36 an association that echoes findings in other cancers characterized by a deregulated prostaglandin network, such as breast and colo-rectal. 37,38 The link between obesity and prostaglandin metabolism has several potential explanations, including increased availability of substrate and IGF (insulin growth factor)-mediated up-regulation of prostaglandin metabolism. 39 Finally, the beneficial properties of some drugs employed in the treatment of MM, most notably thalidomide and immunomodulatory drugs (IMiDs) might also depend on effective inhibition of the COX-2 pathway, as outlined in a recent paper by Fujita et al 40 COX-2 involvement in MM is obviously a strong indication of this pathway's potential role in other hematologic cancers, but the literature is limited in this field.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Obesity is commonly associated with hyperinsulinemia (as measured by the Homeostatic Model Assessment [HOMA] score), 8 insulin resistance, and alterations in levels of adipokines such as adiponectin, all of which are associated with an increased risk of developing pre-and postmenopausal breast cancer. [9][10][11][12] Some studies have also demonstrated that elevated insulin levels and hyperinsulinemia are associated with poor prognosis in patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Other Body Size Indicators (BSI), obtained from weight (W) and height (H), have also been considered in breast cancer prognosis, including weight itself [12][13][14][15][16][17][18][19], Ideal Weight Ratio (IWR) [18,[20][21][22] and Body Surface Area (BSA) [12,18]. Kyogoku et al [18] showed that there are strong quantitative correlations between BSI themselves, whilst significant multivariate breast cancer prognosis effects were observed when BSI were coded as categorical variables.…”
Section: Introductionmentioning
confidence: 99%